Assessing Patterns of Tourism Seasonality in a Mixed Heritage Island Site - SHUMKA, Laura (Journal of Environmental Management and Tourism; Vol 15 No 4 (2024): JEMT, Volume XV, Issue 4(76), Winter 2024DO - 10.14505/jemt.v15.4(76).02, 2024)
The main purpose of the paper is to make a ground investigation on island integrity and factors that are threatening conservation status. The island itself is part of a protected area i.e. National Park Prespa proclaimed in 1999 in Albania, while it holds other important designations as Ramsar site, and Biosphere Reserve. This approach looks primarily on particular impacts caused by tourism seasonality due to climate and geographic location of an iconic small island since it holds one of the regional most spectacular church of Post-Byzantine periods. Further on, the research examines motivation of tourist for visiting the island, considering resources as religion monuments, nature values, landscape and others. Also it examines seasonal patterns in tourism in terms of tourist arrivals mostly via small boats. To that fact, this case of analyze is studied by employing dedicated questionnaire and Gini coefficient along with Seasonality Indicator aiming to cover a time-frame of past ten years.